Community Attitudes Towards People with Mental Disorders (ODGJ) in terms of information sources and experiences of meeting ODGJ in RW 9 Kelurahan Tanggung, Blitar City - Nawang Wulandari; Danang Candra Wiratama (STIKes Patria Husada Blitar, 2020)
Negative knowledge and experience of people with mental disorder (ODGJ) tend to form negative attitude. Many residents still discriminate, such as social isolation. This research aimed to determine people’s attitude towards ODGJ in terms of meeting experienced and the sources of information they get. This research was observational analytic with cross sectional approach. The population of this research was all households in RW 9 Kelurahan Tanggung Blitar City of 199 households, with a sample size of 120 households taken by purposive sampling technique. Attitude data were collected using the Community Attitudes toward Mentally III (CAMI III) questionnaire and analyzed using the Spearman rho correlation test. The results of the analysis showed that attitudes of towards ODGJ in terms of sources of information they have obtained with p value 0,890, and attitudes of households with experience meeting ODGJ with p value 0,470, p value>0.05 which meant that there was no correlation between attitudes and information sources experience meeting ODGJ in RW 9 Kelurahan Tanggung Blitar City. Based on these results, it is necessary to carry out promotional activities in mental health services to form a positive attitude towards people with ODGJ.